STABILITY ANALYSIS OF ROCK BLOCKS WITH ENTIRE SPHERE STEREOGRAPHIC PROJECTION BASED ON THE BLOCK THEORY: A CASE STUDY FOR A TUNNEL ENTRANCE PROJECT - Mboussa, Djohn Josia Weaver; Sun, Shulin; Joseph, Paul Nkombe; Zhang, Yan (International Journal of Research -GRANTHAALAYAH, 2022)
This paper presents a static equilibrium kinematic analysis of rock performed in the tunnel entrance project using entire sphere stereographic projection under block theory. The objective of this study is to improve the predictive analysis of rock masses in terms of stability in rock masses area. Different key blocks with failure modes are determined. The conventional upper hemisphere stereographic projection is also employed for comparative analysis. Based on the findings, it was concluded that the planar failure is not probable in the case of the kinematic and block theory method in the tunnel entrance area. However, the wedge failure is more probable in both cases of analysis and the number of possible slide blocks in the case of kinematic analysis was found to be less than in the case of block theory; In these conditions, the support system should be provided for the reasons of safety. The comparative analysis shows that the results of block theory analysis are close to reality and provide more precision on the stable and unstable block than the results of kinematic analysis; Moreover, the block theory method using the entire sphere stereographic projection provides more precision on the sliding angle than the use of one sphere stereographic projection. Based on this study, the tunnel entrance is more stable for the dip slope face equal to 45 and not probable for slope face 60˚ and 85˚; but these results were limited in the case of stability analysis under gravitational loading.